PEMBERDAYAAN MASYARAKAT MELALUI PEMASARAN BERBASIS DIGITAL PADA UMKM “BAKUL CRAF” DI BANJAR PADANG TEGAL TENGAH UBUD-GIANYAR - Pramuki, Ni Made Wisni Arie; Kusumawati, Ni Putu Ayu; Ayu, Putu Cita; Hurnaleontina, Putu Nuniek; Yuliantari, Ni Putu Yeni (Jurnal Terapan Abdimas, 2021)
Abstract. This community service program is carried out at Bakul Craf, located in Banjar Padang Tegal Tengah Ubud. This program is implemented with the aim of providing knowledge about the use of digital marketing technology. Bakul Craf is a business engaged in the handicraft sector where the process is still manual. The marketing of these handicrafts is still relatively simple, which is only waiting for guests to visit the gallery. For this reason, more productive marketing is needed by utilizing technology, namely digital marketing technology that uses the internet network to improve its products. Providing training and outreach to partners related to the use of digital marketing technology is a method used by the team so that partners have an interest and desire to take advantage of technology. In the first stage, the team provided education related to the importance of using digital technology in marketing handicraft products. The second stage, the team helps partners create accounts in the market place by displaying their craft products. The third stage, the team provides training to partners in operating the menus in the market place. The hope of this activity is that partners can do online marketing and promotion so that their production results can be more widely known and can increase sales which will also have an impact on increasing the revenue of Craf's basket partners.  Abstrak. Program pengabdian kepada masyarakat ini dilaksanakan di Bakul Craf yang berlokasi di Banjar Padang Tegal Tengah Ubud. Program ini dilaksanakan dengan tujuan memberikan pengetahuan mengenai manfaat penggunaan teknologi digital marketing. Bakul Craf merupakan usaha yang bergerak di bidang kerajinan dimana dalam proses pengerjaanya masih secara manual. Pemasaran hasil kerajinan ini tergolong masih sederhana, yaitu hanya menunggu tamu berkunjung kegaleri. Untuk itu diperlukan pemasaran yang lebih produktif dengan memanfaatkan kemajuan teknologi yaitu teknologi digital marketing yang memanfaatkan jaringan internet untuk mempromosikan produknya. Memberikan pelatihan dan penyuluhan terhadap mitra terkait dengan pemanfaatan teknologi digital marketing merupakan metode yang tim gunakan agar mitra memiliki minat dan keinginan untuk memanfaatkan teknologi. Pada tahap pertama, tim memberikan edukasi terkait dengan betapa pentingnya pemanfaatan teknologi digital didalam memasarkan produk hasil kerajinan. Tahap kedua tim membantu mitra membuatkan akun di market place dengan menampilkan produk-produk kerajinannya. Tahap ketiga tim memberikan pelatihan terhadap mitra dalam mengoperasikan menu-menu yang ada didalam market place tersebut. Harapan dari kegiatan ini adalah mitra dapat melakukan pemasaran dan promosi secara online sehingga hasil produksinya dapat dikenal lebih luas sehingga dapat meningkatkan penjualan yang juga akan berdampak pada peningkatan pendapatan mitra bakul craf.